A multi-method approach for the integrative assessment of soil functions: Application on a coastal mountainous site of the Philippines. (15th June 2020) - Dingkuhn, Elsa L.; Wezel, Alexander; Bianchi, Felix J.J.A.; Groot, Jeroen C.J.; Wagner, Adrian; Yap, Helen T.; Schulte, Rogier P.O.
Abstract: The projected increase of the world's population and the sustainability challenges the agricultural sector is facing, call for the enhancement of multi-functionality in agriculture in order to simultaneously provide food while meeting environmental targets. Here, we use the Functional Land Management (FLM) framework to assess the supply of and the demand for soil functions to inform agri-environmental policy for Udalo, a mountainous site in the Philippines. As many emerging communities in developing nations, Udalo is on the cusp of rapid development due to the construction of a major road increasing its accessibility and attractiveness for land investment. We assessed the supply of four soil functions in relation to six land-use types and four slope categories. The function "productivity" was assessed by interviews with 128 farmers, "habitat for biodiversity" by a vegetation survey, and "soil conservation" and "water conservation" via a literature review. The demand for functions was first assessed from the "top-down" policy perspective via interviews and reviews of policy targets, then complemented by integrating the local "bottom-up" demands for functions. These were assessed by applying a Q methodology, providing insights in the prioritisation of functions from the perspective of 22 local actors. Maps of supply and demands were generated for each function: supply maps by overlaying land use and slope category, top-down demand maps from administrative zoning/land-use plans, and bottom-up demand maps from local actors designation of geomorphological areas. Our results revealed contrasting demands for functions, as well as a heterogeneous spatial distribution of supply and demands. Discrepancies emerged (i) between supply and demand, (ii) between bottom-up (local) demands and the top-down (policy driven) demand, and (iii) among local actors perspectives. Our study indicates that discrepancies are not necessarily conflicting, but can uncover pathways for defining compromises, representing attainable policy entry points. Not one single development model can meet the needs of every stakeholder; however, a combination of land uses and management strategies can meet divergent interests and allow for optimisation of functions. This integrative approach of FLM provides a socially embedded biophysical analysis and is a valuable tool for the design of customized land-use and agri-environmental policies. Highlights: We refine the Functional Land Management framework to an integrative approach to assess soil functions and foodscapes. Soil function demands differ between policy-driven (top-down) demand and local (bottom-up) demands, and among local actors. Diverging demands and perceptions occur but also consensus and synergies constituting attainable entry points for policy intervention. Discrepancies in demands can uncover pathways towards compromises. A combination of land uses and management strategies is needed to meet divergent interests.